2016
DOI: 10.3390/antiox5020014
|View full text |Cite
|
Sign up to set email alerts
|

Development of Antioxidant COX-2 Inhibitors as Radioprotective Agents for Radiation Therapy—A Hypothesis-Driven Review

Abstract: Radiation therapy (RT) evolved to be a primary treatment modality for cancer patients. Unfortunately, the cure or relief of symptoms is still accompanied by radiation-induced side effects with severe acute and late pathophysiological consequences. Inhibitors of cyclooxygenase-2 (COX-2) are potentially useful in this regard because radioprotection of normal tissue and/or radiosensitizing effects on tumor tissue have been described for several compounds of this structurally diverse class. This review aims to sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 215 publications
(271 reference statements)
0
46
0
Order By: Relevance
“…Weyemi et al showed that inactivation of both NOX4 and NOX5 can mitigate ROS production and oxidative DNA damage in irradiated human fibroblast cells [24]. In animal model, it has shown that upregulation of prooxidant enzymes such as NOX1, NOX4, COX-2, iNOS and also increased superoxide production by mitochondria are involved in the development of pneumonitis and fibrosis [25][26][27]. Similar results have shown for intestinal cells, vascular endothelial cells, mice brain, etc [28][29][30].…”
Section: Molecular Mechanisms For Continuous Ros Production Followingmentioning
confidence: 74%
“…Weyemi et al showed that inactivation of both NOX4 and NOX5 can mitigate ROS production and oxidative DNA damage in irradiated human fibroblast cells [24]. In animal model, it has shown that upregulation of prooxidant enzymes such as NOX1, NOX4, COX-2, iNOS and also increased superoxide production by mitochondria are involved in the development of pneumonitis and fibrosis [25][26][27]. Similar results have shown for intestinal cells, vascular endothelial cells, mice brain, etc [28][29][30].…”
Section: Molecular Mechanisms For Continuous Ros Production Followingmentioning
confidence: 74%
“…55 Research evidence also shows that anti-oxidants can suppress the levels of COX-2 and alleviate inflammatory response. 56,57 COX-2 expression after nervous injury has been known to play an important major role in peripheral and central sensitization, by altering the excitability of the nociceptor peripheral terminal. However.…”
Section: Cyclooxygenase 2 Protein Analysismentioning
confidence: 99%
“…PGE2 increases intracellular cAMP levels which activates protein kinase A (PKA) and phosphatidylinositol 3-kinase (PI3K) enzymes. PGE2 increases the level of Bcl-2 in adenocarcinoma and activates MAPK pathway through transactivates EGFR by increase in amphiregulin levels as a well-known EGFR ligand [56, 60, 61]. Yamakie et al reported that PGE2 activated sarcoma kinase in non-small cell lung cancer through phosphorylation and activation of STAT3 [62].…”
Section: Introductionmentioning
confidence: 99%
“…It inhibits expression of pro-apoptotic proteins including Bad, Bax, and Bim that lead to inactivate caspase cascades and subsequently suppress apoptotic pathway. Therefore it seems that COX-2 inhibitors such as celecoxib might be useful to enhance the therapeutic index of chemoradiation through sensitization of tumor cells and as well as protection of normal cells to IR [56, 60, 61]. Radiosensitivity effect of COX-2 inhibitors will discuss in next section.…”
Section: Introductionmentioning
confidence: 99%